2019
DOI: 10.4103/apc.apc_13_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and prehypertension in schoolchildren from Central India

Abstract: Background: Epidemiological transition with increasing burden of cardiovascular risk factors is evident not only in adults but also in children. The data on the prevalence of prehypertension and hypertension in children show large regional differences in India and such data are not available from Central India. We, therefore, conducted a large cross-sectional study in Indore to determine the distribution of blood pressure (BP) and the prevalence of hypertension and prehypertension among schoolchil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…A family history of HTN also proved to be a strong indicator in our study where 20.0% of children having a positive family history had HTN and 10.0% had pre-HTN. This finding is consistent with an Indian and a Nigerian study [27][28]. There has been no gender or nationality variation in our study.…”
Section: Discussionsupporting
confidence: 93%
“…A family history of HTN also proved to be a strong indicator in our study where 20.0% of children having a positive family history had HTN and 10.0% had pre-HTN. This finding is consistent with an Indian and a Nigerian study [27][28]. There has been no gender or nationality variation in our study.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of high BP noted in the CNNS in the current study is greater than that reported in most studies from India, although previous estimates were variable, ranging from 2.2% to 25.1%. In one of the largest cross-sectional studies that was conducted in central India, involving 11 312 children between 5 and 15 years of age (5305 girls and 6007 boys), high BP was found in 6.8% of the boys and 7.0% of the girls . In a meta-analysis of 25 published studies from India (total sample of 27 682 participants), the pooled estimate of prevalence of high BP was 7.6% (95% CI, 6.1%-9.1%).…”
Section: Discussionmentioning
confidence: 97%
“…In one of the largest cross-sectional studies that was conducted in central India, involving 11 312 children between 5 and 15 years of age (5305 girls and 6007 boys), high BP was found in 6.8% of the boys and 7.0% of the girls. 22 In a meta-analysis 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, the prevalence of type 2 diabetes has increased between 1980 and 2014 [ 3 ], but at higher rates in LMICs [ 1 ]. The prevalence of childhood hypertension in Central India is reported to be 6.8–7.0% [ 4 ] rising to 9.5% in Chennai [ 5 ], compared to 4% globally. Furthermore, mortality occurs earlier in LMICs, with the number of years spent living with these conditions increasing [ 2 , 3 ], escalating the societal and individual health burden.…”
Section: Introductionmentioning
confidence: 99%